The effects of on-pump and off-pump coronary artery bypass surgery on respiratory function in the early postoperative period - Chiarenza, F; Tsoutsouras, T; Cassisi, C; Santonocito, C; Gerry, S; Astuto, M; George, S; Sanfilippo, F (SAGE Publications, 2017)
Background Respiratory complications are common after cardiac surgery and the use of extracorporeal circulation is one of the main causes of lung injury. We hypothesized a better postoperative respiratory function in OFF-pump coronary-artery bypass grafting (OPCABG) as compared with “ON-pump” (ONCABG). Methods This is a retrospective, single centre study at a Cardiothoracic intensive care unit (ICU) in a Tertiary University Hospital. Consecutive data on 339 patients undergoing elective CABG (n=215 ONCABG, n=124 OPCABG) were collected for one-year from the ICU electronic medical records. We compared respiratory variables (PaO2, PaO2/FiO2ratio, SaO2and PaCO2) at seven predefined time-points (ICU admission, 1st-3rd-6th-12th-18th-24th postoperative hour). We also evaluated time-to-extubation, rates of re-intubation and use of non-invasive ventilation (NIV). We used mixed-effects linear regression models (with time as random-effect for clustering of repeated measures) adjusted for a pre-determined set of covariates. Results The values of PaO2and PaO2/FiO2 were significantly higher in the OPCABG group only at ICU admission (mean differences: 9.7 mmHg, 95%CI 3.1-16.2; and 27, 95%CI 6.1-47.7, respectively). The OPCABG group showed higher PaCO2, overall (p=0.02) and at ICU admission (mean difference 1.8 mmHg, 95%CI 0.6-3), although mean values were always within normal range in both groups. No differences were seen in SaO2values, time-to-extubation, rate of re-intubation rate and use of postoperative NIV. Extubation rate was higher in OPCABG only at the 12th postoperative hour (92% vs ONCABG 82%, p=0.02). Conclusions OPCABG showed only marginal improvements of unlikelyclinical meaning.in oxygenation as compared to ONCABG in elective low-risk patients.